The Efforts to Increase the Toeic Scores of Semester V Students Based on Information Technology at Polytechnic LP3I Bekasi - Jajang Setiawa*; Retno Setya Budiasngrum; Ali Satri Effendi; Andri Irawan (Universitas Syiah Kuala, 2023)
TOEIC is a test to measure English proficiency needed in the workplace. Many workplaces use this test to find a good candidate to hire. Hence, someone needs to prepare themself to pass the test. The study aims to discover whether preparation by giving TOEIC training using technology can improve the TOEIC scores of the students at the LP3I Polytechnic Bekasi. This research is a quantitative study. The result shows that the TOEIC scores of the students improve after the training. It means training preparation using technology before the test improves students' TOEIC scores..